THE RELATIONSHIP OF KNOWLEDGE AND FAMILIY SUPPORT WITH SCHIZOPHRENIA PATIENT MEDICATION COMPLIANCE CONTROL IN RSJD JAMBI PROVINCE 2018 - Netha Damayantie; Rusmimpong Rusmimpong; Elly A (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
Other psychiatric illnesses such as schizophrenia need a long time to recover. The main problem in patients post hospitalization is the compliance control or compliance in taking the medication. Patient compliance to control the patient's own health is influenced by, family support, social support, and also support health workers. This research uses a cross sectional design to know the relationship of knowledge and support families with schizophrenia patient compliance control in RSJD Province Jambi. Population is a whole family of schizophrenia patients in Poly in 2017 totaled 11877 people, with a sample of 96 people who do control the patient's family selected by accidental sampling. Research instrument in the form of sheets of ceklist control and a questionnaire about the knowledge and support of the family. The research was carried out in July 2018. The data analysis done in a univariate and bivariat (Chi-square) The research results obtained over most respondents do not comply do control (58.3%), has a less good knowledge (50%) and has a positive family support (52.1%) about the repeated control patients of schizophrenia. There is a connection between the knowledge of families with schizophrenia patient compliance control (p-value = 0.00). There is a relationship between family support with compliance control patients of schizophrenia (p-value = 0.00)